1997
DOI: 10.1001/archinte.1997.00440270035003
|View full text |Cite
|
Sign up to set email alerts
|

Seizures and Epilepsy in the Elderly

Abstract: Seizures and epilepsy in the elderly are an important and increasingly common clinical problem. Major known causes include cerebrovascular disease, brain tumor, degenerative disorders such as Alzheimer disease and cerebral amyloid angiopathy, and toxic-metabolic syndromes such as nonketotic hyperglycemia, postcardiac arrest, and drug-induced seizures. Recognition of seizures may be complicated by relatively unique clinical presentations and differential diagnosis. Nonconvulsive status epilepticus may present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 175 publications
2
37
0
4
Order By: Relevance
“…24 Another study by Christine et al, found cortical infarcts in 20% cases followed by tumor (10%), cryptic arteriovenous malformation (4%) and mesiotemporal sclerosis (2%). 26 In our study, CT brain was abnormal in 95 (61.7%) patients and 61 (59.7%) patients had abnormal MRI brain. This finding of neuroimaging was due to selection of patients for MRI brain study.…”
Section: Discussionsupporting
confidence: 48%
“…24 Another study by Christine et al, found cortical infarcts in 20% cases followed by tumor (10%), cryptic arteriovenous malformation (4%) and mesiotemporal sclerosis (2%). 26 In our study, CT brain was abnormal in 95 (61.7%) patients and 61 (59.7%) patients had abnormal MRI brain. This finding of neuroimaging was due to selection of patients for MRI brain study.…”
Section: Discussionsupporting
confidence: 48%
“…Transient global amnesia (TGA) can be confused with seizure activity [24] . TGA is a clinical syndrome characterized by a number of clinical features: a clear-cut anterograde amnesia with no clouding of consciousness or loss of personal identity, the absence of neurological signs or deficit, no features suggesting epilepsy or active epilepsy, no recent head injury, and resolution within 24 h [25] .…”
Section: Seizures In Elderly Patients With Dementia: Diagnosismentioning
confidence: 99%
“…An increased incidence of epilepsy occurs in the elderly population, representing a second peak in incidence of epilepsy in all age groups after an initial peak in the first years of life (1)(2)(3)(4)(5). Whereas a number of studies have examined the etiology of epilepsy in the elderly, there are few data on the nature of typical nonepileptic paroxysmal events in older patients.…”
mentioning
confidence: 99%